2022
DOI: 10.3390/sym14112269
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Sensitivity Analysis of the COVID-19 Spread with Comorbid Diseases

Abstract: This research investigates a model of the spread of COVID-19 in Indonesia by paying attention to comorbid disease, self-quarantine, government-provided quarantine, and vaccination factors. The symmetrical aspects of the model are studied. The evaluation of the model reveals non-endemic and endemic equilibrium points and the basic reproduction number (BRN). We provide the local and global stability analysis of the equilibriums. According to the sensitivity analysis of the BRN, the key parameters impacting the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…37) Finally, since the arithmetic mean is greater or equal to the geometric mean as applied by [22,23,24], it follows that:…”
Section: Global Stability Of Covid-19 Endemic Equilibrium Pointmentioning
confidence: 99%
“…37) Finally, since the arithmetic mean is greater or equal to the geometric mean as applied by [22,23,24], it follows that:…”
Section: Global Stability Of Covid-19 Endemic Equilibrium Pointmentioning
confidence: 99%
“…If the fundamental reproduction number is smaller than one, the dynamic model of COVID-19 in China with recruitment growth rate logistics spread internationally, and an asymptotically stable non-endemic equilibrium point [6]. The COVID-19 mathematical model study also took into account comorbid and non-comorbid [7], symptomatic and asymptomatic disorders in Indonesia [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It could be concluded that the prevention strategy for dengue infection could prevent COVID-19 infection among 870,000 new cases while controls against dengue and controls against COVID-19 could only considerably reduce the infection. Nainggolan and Ansori [35] studied a model of the spread of COVID-19 in Indonesia. Importance was given to quarantine for infectious persons.…”
Section: Introductionmentioning
confidence: 99%